Interest in Switching to On-Demand HIV Pre-Exposure Prophylaxis (PrEP) Among Australian Users of Daily PrEP: An Online Survey. (14th June 2019) - Cornelisse, Vincent J; Lal, Luxi; Price, Brian; Ryan, Kathleen E; Bell, Charlotte; Owen, Louise; Wright, Edwina J
Abstract: We surveyed 970 PrEPX study participants to evaluate interest in switching from daily to on-demand PrEP in a study setting. Interested respondents (n = 469, 48%) more commonly reported PrEP cessation (adjusted odds ratio [aOR], 3.0; P < .001), difficulty with adherence (aOR, 1.6; P = .029), infrequent sex (aOR, 3.7; P < .001), and toxicity concerns (aOR, 2.7; P < .001).